The Marketing Strategy of International Cosmetic Company In Thailand: A Case Study of Kanebo Cosmetics - Dulgaiphan, Miss Thaphatkorn (2009)
In the era of globalization where there are many opportunities for firms to improve current business practices, the internalization of international firms is a normal practice. The companies in cosmetic industry are seeking ways to improve its performance and its reputation worldwide. The purpose of this dissertation is to study marketing strategy of international cosmetics companies by taking Kanebo Cosmetics (Thailand) as an example. Marketing analyses including the standardization of marketing strategy, market segmentation and targeting, branding and brand positioning, marketing mix and customer relationship management provide theoretical frameworks for the study of this dissertation.